Social Anxiety Among Generation Z in Bandung: A Descriptive Cross-Sectional Study - Pratama, Naufal Aldian; Permana, Rizka Hadian; Cahyati, Yanti (PT. Pubsains Nur Cendekia, 2025)
Background: Generation Z is a group raised in a digital ecosystem and exposed to social media early on. Their dependence on online interactions makes them vulnerable to social comparison and digital social pressure. This condition risks reinforcing patterns of social avoidance associated with social anxiety. Aim: To describe the level of social anxiety among Generation Z in Bandung City based on the variables of gender, age, employment status, duration of social media use, and type of social media used. Method: The method used is a descriptive quantitative approach with a cross-sectional design. Data were collected using an online questionnaire and the Liebowitz Social Anxiety Scale (LSAS-SR) from 8 to 15 May 2025, and were subsequently analyzed using descriptive statistical methods to categorize the levels of social anxiety among Generation Z in Bandung. Results: Most respondents were found to experience social anxiety in the moderate category, with 56.38% classified as moderate, followed by 21.58% marked and 18.06% mild. The moderate level also dominated across gender, age, employment status, duration of social media use, and preferred platforms, indicating that moderate social anxiety is consistently the most prevalent among Generation Z in Bandung. Conclusion: These results reflect that social anxiety is a fairly common issue among Generation Z and tends to be evenly distributed across various individual characteristics and digital behaviors. This study recommends the need for education regarding healthy social media use and strengthening social skills to prevent the development of more severe social anxiety symptoms.